NAHDLATUL ULAMA DAN NEGARA BANGSA - Muhammad Adnan (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
Nahdlatul Ulama (NU), as one of the pillars of Indonesian Muslim Organization who participated in formulating a national consensus of Indonesia as a nation state, is known to have a moderate credo of Islam and capable of maintaining harmony and continuity of life of the Indonesian nation state. However, in line with the increasing threat of transnational Islamic forces that bring radical ideas and even terrorism in the people and the nation, the challenges faced by Indonesia is not only a threat to social harmony that has been established, but also his destiny as a country describes nation-state. This paper explains NU’s approach toward Islamic law which is called fiqhi approach in deciding Indonesia as a nation state; NU consistency with these choices so that believes that the Unitary Republic of Indonesia (NKRI) is the final form of the struggle of Indonesian Muslims; and its ability to use fiqhi approach to address the threat to the nation of Indonesia.